The Efficacy of Cognitive Stimulation on Depression and Cognition in Elderly Patients with Cognitive Impairment: A Retrospective Cohort Study - Filipin, Federerico (2015)
Cognitive decline due to neurodegenerative diseases is a prevalent worldwide problem. Both pharmacological and non-pharmacological treatments to improve, delay or stop disease progression are of vital importance. Cognitive stimulation is frequently used in clinical practice; however, there are few studies that demonstrate its efficacy. Aim: To evaluate the efficacy of cognitive stimulation in patients with mild cognitive impairment (CDR = 0.5) and dementia (CDR = 1). Methods: A retrospective cohort study was performed. Patients with cognitive impairment receiving weekly cognitive stimulation (16 or 24 sessions) were evaluated with a complete neuropsychological battery before and after the stimulation program. Each stimulation session was carried out by a trained neuropsychologist. Results: Forty two patients receiving cognitive stimulation were evaluated over a period of 12.53 months (SD 5.5). Patients were grouped as 11 amnesic mild cognitive impairment (aMCI), 23 multi domain mild cognitive impairment (mMCI) and 8 Mild Alzheimer’s Dementia (CDR 1). None of the groups improved their cognitive functions after the cognitive stimulation program. MCI group was also divided according to their global intelligence quotient (IQ) into two groups: low (IQ < 98.5) and high (IQ > 98.5). Each group was compared before and after the stimulation program and no significant difference was found (p ≥ 0.05). Moreover, MCI group was also analyzed according to the duration of the stimulation program: less than 9, between 9 and 13 and more than 13 months. Different duration groups were compared before and after the cognitive stimulation program and no significant differences were found. Depression, anxiety and subjective memory symptoms were also analysed and neither improvement nor worsening could be demonstrated. Conclusions: Patients remained stable, both in cognitive and behavioural domains, for more than 18 months. However, no significant cognitive or behavioural improvement can be reported in these patients after the stimulation program (duration time: 12.53 months SD 5.5).